DESAIN DAN IMPLEMENTASI VIRTUALISASI BERBASIS DOCKER UNTUK DEPLOYMENT APLKASI WEB - Sulastri Apridayanti; Isnawaty Isnawaty; Rizal Adi Saputra (Informatics Engineering Department of Halu Oleo University, 2018)
Building a program through virtualization, developers usually run virtualization on the server so that the process of making the program can run on various platforms and hardware configurations. The problem with virtualization is the need to set up a complete operating system, including the various applications that the system brings. You can imagine with the number of virtualization that runs on a server will burden the system.Docker is one platform built on container technology. Docker is an open-source project that provides an open platform for developers and sysadmins to build, package and run applications anywhere as a lightweight container.The results obtained in research conducted is a web application wherein implementing server virtualization techniques using Docker for application deployment is successful. The application used is a trading application that is stored on Docker Server where both Client successfully using the application on different platforms that are Windows 7 and Windows 8 without experiencing any obstacles at all.Keywords— Virtualization, Docker, Web Application